Analisis Kompetensi Profesionalisme Guru Madrasah Aliyah - Warni, Masnely (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2021)
Education is an effort made to build one's personality so that it can develop for the better. The professionalism of teachers can be seen from their academic qualifications and teaching experience. If a teacher's academic qualifications have met the existing provisions and standards, then he or she will have the appropriate competencies and are needed in managing learning while at school. Educational institutions are expected to be able to realize their role effectively with excellence in leadership, staff, educators, teaching and learning processes, development of educators and education personnel, curriculum, school climate, and involvement of parents and the community